Acoustic problems in multi-storey residential buildings raised by means of industrialized technology methods - SADOWSKI, Jerzy (Archives of Acoustics, 1985)
The paper comprises results of subjective (social survey) and objective tests (measurements) of the acoustic climate in multi-storey buildings raised by industrialized methods. On the basis of performed tests the paper also discusses factors influencing the sound insulation in dwellings, as well as opinions concerning designing.